2011
DOI: 10.1021/es2014727
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Analysis with Chiral Cyclodextrin Phases Reveals the Enantioselective Formation of Hydroxylated Polychlorinated Biphenyls by Rat Liver Microsomes

Abstract: Chiral PCB congeners are major components of PCB mixtures and undergo enantioselective biotransformation to hydroxylated (OH-)PCBs by cytochrome P450 enzymes. While it is known that biotransformation results in an enantiomeric enrichment of the parent PCB, it is currently unknown if OH-PCBs are formed enantioselectively. The present study screened seven commercial capillary gas chromatography columns containing modified β- or γ-cyclodextrins for their potential to separate the atropisomers of methylated deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
139
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 47 publications
(158 citation statements)
references
References 35 publications
11
139
8
Order By: Relevance
“…Incubations of individual, racemic PCB congeners or a mixture of several C-PCBs with rat CYP2B1 show preferential transformation of E 2 -PCB 45, (−)-PCB 84, E 1 -PCB 91, E 2 -PCB 95, (−)-PCB 132, (+)-PCB 136 and (−)-PCB 149. The same direction of atropisomeric enrichment is observed in rat liver microsomal incubations (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Wu et al 2011) and, for PCB 136, in rat liver tissue slices (Wu et al 2013b). At the same time, the formation of HO-PCB metabolites by rat P450 enzymes is atropselective, thus resulting in an atropisomeric enrichment of the HO-PCBs.…”
Section: Metabolism Of C-pcbs To Ho-pcbssupporting
confidence: 62%
See 4 more Smart Citations
“…Incubations of individual, racemic PCB congeners or a mixture of several C-PCBs with rat CYP2B1 show preferential transformation of E 2 -PCB 45, (−)-PCB 84, E 1 -PCB 91, E 2 -PCB 95, (−)-PCB 132, (+)-PCB 136 and (−)-PCB 149. The same direction of atropisomeric enrichment is observed in rat liver microsomal incubations (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Wu et al 2011) and, for PCB 136, in rat liver tissue slices (Wu et al 2013b). At the same time, the formation of HO-PCB metabolites by rat P450 enzymes is atropselective, thus resulting in an atropisomeric enrichment of the HO-PCBs.…”
Section: Metabolism Of C-pcbs To Ho-pcbssupporting
confidence: 62%
“…A convenient nomenclature for PCB metabolites has been proposed by Maervoet et al and, as shown for PCB 136 in Fig 3, will be used throughout this manuscript (Maervoet et al 2004). The oxidation of C-PCBs, in particular those with a 2,3,6-trichloro substitution pattern in one phenyl ring, to HO-PCBs has been studied extensively using recombinant enzymes (Lu et al 2013, Lu and Wong 2011, Waller et al 1999, Warner et al 2009), hepatic microsomes (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Schnellmann et al 1983, Wu et al 2014, Wu et al 2011), isolated hepatocytes (Vickers et al 1986) and, liver, hippocampus and skin slices (Garner et al 2006, Wu et al 2013a, Wu et al 2013b) obtained from mammalian species. To the best of our knowledge, the oxidation of C-PCBs in non-mammalian species, such as amphibians, fish or avian species, has not been investigated to date.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
See 3 more Smart Citations